PERSEPSI KONSUMEN TERHADAP AGROWISATA SALAK PONDOH DI KECAMATAN TURI KABUPATEN SLEMAN - Rencia Aggraini; Ken Suratiyah; Dwidjono Hadi Darwanto (Department of Agricultural Socio-Economics Faculty of Agriculture Universitas Gadjah Mada, 2010)
The research ainm was to know the consumer perception tward the avaibility of Salak Pondoh Agritourism (WASP) facilities, its service condition, and its view condition. This research used analytical descriptive method and to get 60 sample/respondens used accidental sampling method. The data that has been taken are primary and secondary data which obtained from the result of interviewing the company officer, the result of questioning papers, the organization structure, the map of WASP, and the sun of visitors per year. The result of the research showed that consumers had a good perception toward the avaibility of WASP facilities which are agricultural commodity, transportation, sheltered place, information, and communication; consumers had a good perception toward WASP services condition, it meant that Salak Pondoh Agritourism had a good quality of its services; and consumers had an unwell perception toward the WASP view condition. Suggestions that been given to WASP are to maintain the available facilities in WASP more and to add few more facilities which have already or haven’t existed, those are tour guides, public telephone, fishing hool renting place, toilet, and garden seats.